Status of antioxidant defense system for detoxification of arsenic in Brassica juncea (L.) - Ansari, Mohd. Kafeel Ahmed; Zia, Munir Hussain; Ahmad, Altaf; Aref, Ibrahim Mohammed; Fatma, Tasneem; Iqbal, Muhammad; Owens, Gary (Ecoprint: An International Journal of Ecology, 2016)
The content of arsenic (As), a naturally occurring toxic element found in soils worldwide, has gone substantially high in agricultural soils due to various anthropogenic activities. The responses of seed germination, seedling growth, photosynthetic pigments and the components of the ascorbateglutathione (AsA-GSH) pathway were analyzed in Indian mustard [Brassica juncea (L.) Czern.] cultivar Pusa Jai Kisan, treated with 0, 5, 10, 25 and 50 μM As concentrations in a hydroponic system. While a significant increment in lipid peroxidation and H2O2 generation was observed at higher concentrations after 2 and 5 days of stress imposition. Significant increases were also observed in superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and glutathione reductase (GR) activities under the influence of 25 and 50 μM As concentrations after 2 and 5 d stress impositions. There was a steep increase in the ascorbic acid (AsA) content between 2 and 5 d after As treatment, while glutathione (GSH) content increased significantly after 5-d-exposure. Accumulation of As was more in shoot than in root. This study clearly demonstrated that high concentration (50 μM) of As inhibited growth and caused oxidative stress and that the AsA-GSH pathway has an important role in cellular defense against As in Brassica juncea (L.). ECOPRINT 22: 7-19, 2015